Differences in the clinical course, laboratory and radiological findings of COVID-19 infection between male, female and pregnant patients in demographically homogeneous groups (Annals of Medical Research, 2023)
Aim: This study examines for any differences in the clinical course, laboratory and radiological findings of COVID-19 infection between male, female and pregnant patients in similar age groups.Materials and Methods: This  retrospective study involved a review of the data of patients treated between March 2020 and May 2021, included a total of 528 cases (193 pregnant females, 170 non-pregnant females and 165 males) aged 18–40 years with RT-PCR-confirmed COVID-19.Results: A comparison of the three demographically homogeneous groups revealed more common symptomatic infection at admission in the male patient group than in the other two patient groups (p